A people's history of Christianity / 6 Modern Christianity to 1900 / Amanda Porterfield, editor - Porterfield, Amanda (A people's history of Christianity, 2010)
Death, secularization, and doubt / Carlos Eire -- Controlling and Christianizing sex / Peter Gardella -- Economic change and emotional life / John Corrigan -- Vulgar/popular science / Ronald L. Numbers -- Tropical Christianity in Brazil / H.B. Cavalcanti -- Iconic piety in Russia / Vera Shevzov -- From Puritanism to Evangelicalism / Douglas Winiarski -- Domestic piety in colonial New England / Ava Chamberlain -- Gendering Christianity / Marilyn Westercamp -- Slave Christianity / Charles H. Lippy -- Spirituals and the quest for freedom / Cheryl Kirk-Duggan